2009
DOI: 10.1093/jac/dkp292
|View full text |Cite
|
Sign up to set email alerts
|

Isoniazid and rifampicin resistance-associated mutations in Mycobacterium tuberculosis isolates from Yangon, Myanmar: implications for rapid molecular testing

Abstract: This study provides the first molecular characterization of isoniazid- and rifampicin-resistant M. tuberculosis isolates from Myanmar and gives information on the molecular basis for rifampicin and isoniazid drug resistance in M. tuberculosis. The study generates useful information for the development of potential rapid molecular drug susceptibility tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
18
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 25 publications
8
18
1
Order By: Relevance
“…The combined sensitivity of katG and inhA promoter mutations for the detection of the phenotypic INH r that we observed (96%) is consistent with the cumulative frequency of these mutations in the published literature (24)(25)(26). There are, however, some recent studies on international isolates which suggest that using only katG and inhA promoter SNPs will yield sensitivities of Ͻ90% due to isolates that do not have these SNPs (27).…”
Section: Discussionsupporting
confidence: 89%
“…The combined sensitivity of katG and inhA promoter mutations for the detection of the phenotypic INH r that we observed (96%) is consistent with the cumulative frequency of these mutations in the published literature (24)(25)(26). There are, however, some recent studies on international isolates which suggest that using only katG and inhA promoter SNPs will yield sensitivities of Ͻ90% due to isolates that do not have these SNPs (27).…”
Section: Discussionsupporting
confidence: 89%
“…The occurrence of the KatG Ser315Thr alteration among Nepalese isolates was higher than that reported in India (16,22) and in China (4, 10, 12) ( Table 6). Van Soolingen et al (32) reported that strains with amino acid substitutions in katG 315 are more likely to develop resistance to (6,26,31). Several studies from different countries have shown that ca.…”
Section: Discussionmentioning
confidence: 99%
“…13 For INH, several genes, including katG, the promoter of inhA and the intergenic region of oxyR-ahpC, are associated with INH resistance in M. tuberculosis isolates. 13,15 Of those INH resistance targets, the substitution of a single nucleotide at codon 315 of the katG gene is the most frequently identified mutation type, conferring approximately 70% of INH resistant isolates. 15,16 Due to the high prevalence of MDR among TB patients, China has been classified as global "hotspots" of MDR-TB.…”
Section: Introductionmentioning
confidence: 99%
“…13,15 Of those INH resistance targets, the substitution of a single nucleotide at codon 315 of the katG gene is the most frequently identified mutation type, conferring approximately 70% of INH resistant isolates. 15,16 Due to the high prevalence of MDR among TB patients, China has been classified as global "hotspots" of MDR-TB. 2,17,18 Although several molecular epidemiological studies have been performed among MDR strains isolated from different regions of China, the knowledge on molecular characteristics of MDR-TB isolates representative of the whole China is still unknown now.…”
Section: Introductionmentioning
confidence: 99%